Neuroprotective Effect of DAHP via Antiapoptosis in Cerebral Ischemia - Yanhua Qin; Weiming Hu; Yang Yang; Zhiying Hu; Weiyun Li; Marong Fang (Behavioural Neurology)
Aberrant production of nitric oxide following inducible nitric oxide synthase (iNOS) expression has been implicated in cell death and contributes to ischemic brain injury. Tetrahydrobiopterin (BH4) is an essential cofactor of NOS activity. Herein, we evaluated antiapoptotic and anti-inflammatory effects of diamino-6-hydroxypyrimidine (DAHP), a guanosine 5′-triphosphate cyclohydrolase 1 (GTPCH1) inhibitor on focal cerebral ischemia-reperfusion injury by middle cerebral artery occlusion and reperfusion (MCAO) and investigated the underlying mechanism. Sprague-Dawley rats were divided into five groups. Experimental groups were subjected to 1.5 h transient MCAO. T2-weighted imaging was performed to evaluate brain edema lesions in the stroke rats. Infarct volume was estimated by 2,3,5-triphenyltetrazolium chloride (TTC) staining after 24 h reperfusion. Western blotting and immunohistochemistry were performed to detect iNOS, caspase-3, Bcl-2, COX-2, and TNF-α protein expressions. Apoptosis was determined by TUNEL staining. T2 hyperintensity changes were observed in primary ischemic region. DAHP pretreatment significantly suppressed iNOS overexpression, caspase-3, and TNF-α. There was also attenuation of neuronal apoptosis with decrement in proteins Bcl-2 and COX-2 expressions. On the basis of our results, we hypothesize DAHP to have a neuroprotective function against focal cerebral ischemia and might attenuate brain injury by decreasing reactive oxygen species (ROS) production, subsequently inhibiting apoptosis.